Analisis sistem pengendalian internal pada sistem penggajian karyawan (Studi kasus CV Surya Jaya Abadi) - Haryadi, Tri; Triyanto , Eko (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to determine the internal control system at CV Surya Jaya Abadi, the procedures applied in the employee payroll process, and to find out the weaknesses of the procedures that have been implemented. This research uses a descriptive qualitative method with a case study approach, data obtained from observations, interviews, and documentation. The results of this study are the control system at CV Surya Jaya Abadi has been running quite effectively, although there are weaknesses found, among others, there is no separation of duties and authorities related to payroll, everything is done by the HRD department, there is no written internal payroll control system. as a guide in the payroll process, as well as a computerized payroll system that is not yet connected to the attendance system. Payroll problems that occur at CV Surya Jaya Abadi are salary errors, many are caused by human factors, including employees who have not been orderly absent through the fingerprint machine and errors in inputting the components of salary and attendance by the payroll section, namely HRD because the payroll system is separate from absences. Â